“C’è un furto con scasso in ogni vera lettura”. Calvino’s Thefts from Ariosto - Martin McLaughlin (Parole Rubate, 2013)
Calvino’s love for Ariosto throughout his writing life is well known. However, despite this life-long enthusiasm for Ariosto, there are some variations. In a 1980 interview with Tullio Pericoli Calvino used the metaphor of “stealing” words from other texts and discussed notions of artistic thievery, citing his own “thefts” from Ariosto. The article examines how Calvino carries out his thefts, and how he then systematically develops in his own way what he has “stolen”, concentrating on key episodes from Il cavaliere inesistente and Il castello dei destini incrociati. What emerges is that in the first phase of his literary career Calvino was more concerned with the content of the Furioso, while in later years he became fascinated by the poem’s structural and stylistic qualities.